Catalisadores baseados em Fe-C mesoporosos para síntese de Fischer-Tropsch - Cruz, Márcia Gabriely Alves da (2017)
This work deals with the influence of preparation methods of Fe - containing carbon catalysts for Fischer - Tropsch Synthesis (SFT). For these purposes, two series of solids were prepared. The first series was the Fe - based catalysts supported o n polystyrene mesoporous carbon pretreated at dif ferent calcination temperatures. The second series of materials was the solids prepared by distinct preparation methods. All solids were characterized by X - ray diffract ion (XRD) , Raman spectroscopy, s canning and t ransmission electron microcopies (SEM and TEM), textural properties, elemental composition by X - ray dispersive spectroscopy (EDS), temperature programmed reduction (TPR) and X - ray photoelectron spectroscopy (XPS). It was shown that the preexistent carbides phases obtained in the Fe - containing polymeric mesoporous carbons upon using elevated temperatures of calcinations resulted in a solid with good textural and structural properties. However, these materials were not comp letely reoxidized during the SFT reaction while the formation of carbides through the polymeric carbon reaction with magnetite and  or metallic iron resulted in highly active catalysts for SFT . The second series of materials applied copolymer assisted co - p recipitation of iron precursor (CP) , chemical modification of ferrocene (CM) , sol - gel (SG) and wetness impregnation of iron on polymeric carbon (IM) methods . SG method solid resulted in a conversion of syngas up to 56% and productivity of 34 mg hydrocarbon .g cat - 1 .h - 1 at 240 o C and 20 atm. IM gave a Fe/C based catalyst with the highest exposure of active sites, including surface Fe 3+ and Fe 2+ redox sites with great properties in SFT . CM route enabled the formation of hematite and maghemite nanoparticles on ca rbon, which were reduced in situ to magnetite and iron carbide s, the latt er being the most active for the water - gas - shift reaction (RWGS) reaction. It was found that copolymer assisted CP facilitate d the production of large crystals of magnetite, which suf fered sintering and coking in SFT . Among these methods, SG proved to have superior performance due to the good dispersion of Fe, stable magnetite as well as iron carbide and Fe - doped nitrogen carbon phases production.